Partisipasi Masyarakat Dalam Pembangunan Desa - M Wahyuddin; H Mustari; Harna Harna (Universitas Negeri Makassar, 2020)
The purpose of this study was to find out the community participation in the construction of Pattaneteang Village in Tompobulu Subdistrict, Bantaeng Regency and to know the factors that influenced the level of village community participation. This research is research using descriptive qualitative. Methods of collecting data through observation, interviews, and documentation and data analysis carried out data reduction, data presentation, and conclusion drawing. The results showed that community Participation Formed in the Pattaneteang Village community is direct participation in the form of energy and implementation, participation in the form of property or money, participation in the form of ownership and participation of ideas or ideas. The indirect participation in Pattaneteang village from the village head's explanation distinguishes participation into four types, namely first, participation in decision making. Second, participation in implementation. Third, participation in utilization. And Fourth, participation in evaluation. Factors that influence the level of participation in the Pattaneteang Village community are, internally, including age, limited property, education, employment, and income. From the external side, it consists of village government leadership factors, BPD, development supporting equipment/facilities, level of intensity of interaction and level of transparency in the village.